Analisis Korelasi Tingkat Timbal (Pb) dan Kreatinin dalam Darah pada Kelompok Manusia Silver di Wilayah Kediri - Mardiana Prasetyani Putri; Arshy Prodyanatasari M.Pd.; Mely Purnadianty; Novia Agustina; Nita Ermawati (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2026)
Heavy metal exposure, such as lead (Pb), poses a severe threat to human health due to its toxic nature, which can trigger vital organ damage, particularly in the kidneys. The 'silver human' group is at high risk of Pb exposure due to the routine application of metallic paint over their entire bodies. This research aimed to evaluate the correlation between blood lead concentrations and serum creatinine levels as an indicator of kidney function among silver humans in Kediri City. This observational study, utilizing a cross-sectional design, involved six silver human subjects selected through total sampling. Pb analysis was performed using Atomic Absorption Spectrophotometry (AAS), while creatinine levels were assessed using standard laboratory methods. All respondents (100%) exhibited Pb levels within the normal range, with an average of 7.000 µg/dL. However, regarding the creatinine parameter, 50% of the respondents were found to have levels exceeding the normal threshold. Pearson statistical analysis indicated a p-value of 0.785 (p > 0.05). Consequently, no significant correlation was observed between blood lead levels and creatinine concentrations among the research subjects in Kediri City.